Take A Breath: study protocol for a randomized controlled trial of an online group intervention to reduce traumatic stress in parents of children with a life threatening illness or injury. Issue 1 (December 2016) - Rayner, Meredith; Muscara, Frank; Dimovski, Anica; McCarthy, Maria; Yamada, Jackie; Anderson, Vicki; Burke, Kylie; Walser, Robyn; Nicholson, Jan
Abstract Background A substantial proportion of parents whose child is diagnosed with a life-threatening illness, experience high levels of distress that can lead to long-term difficulties in mental health, family functioning and child adjustment. This study evaluates the efficacy of an Acceptance Commitment Therapy-based group intervention designed to reduce distress symptoms in these parents. The program is delivered using videoconferencing to overcome factors that prevent participation in traditional face-to-face therapy. Method/design The study is a randomized control trial of the Take A Breath group intervention for parents demonstrating elevated symptoms of acute stress, delivered via videoconferencing in six 90 min group sessions. Participants are the primary caregivers of children aged 0 to 18 years admitted for a life threatening illness or injury to the Oncology, Cardiology, Neurology or Intensive Care Departments of a tertiary pediatric hospital. Parents will be randomized to intervention or waitlist control 4–10 months after their child's diagnosis. Measures will be collected prior to and immediately post intervention for intervention and waitlist parents to assess program efficacy. Intervention parents will be followed up at 6 months to assess the maintenance of program effects. We predict that intervention parents will show fewer symptoms post intervention than waitlist parents (primary outcomes: traumatic stress, depression, anxiety, stress symptoms), reflecting improvements in the psychological skills addressed in the intervention (mediating factors). It is anticipated that reductions in mental health difficulties for intervention parents will be maintained up to 6 months post-intervention and will be associated with broader improvements in parents' adjustment, child adjustment and child wellbeing (secondary outcomes). Discussion This study is unique in evaluating a group intervention delivered to parents of children affected by of a diverse range life-threatening illness or injury. Online communication technology is employed to reduce participation barriers. If proven efficacious, this trans-diagnostic approach offers the potential for broad use as part of the suite of psychosocial services provided to families through tertiary pediatric settings. Trial registration ACTRN12611000090910 . Trial Registration Date: 14/09/2011 Protocol Date/version: September 2015, version M Study Status: Ongoing